2015
DOI: 10.1039/c5cp00515a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hydrolysis of gas-phase lanthanide and actinide oxide nitrate complexes: a correspondence to trivalent metal ion redox potentials and ionization energies

Abstract: Several lanthanide and actinide tetranitrate ions, M(III)(NO3)4(-), were produced by electrospray ionization and subjected to collision induced dissociation in quadrupole ion trap mass spectrometers. The nature of the MO(NO3)3(-) products that result from NO2 elimination was evaluated by measuring the relative hydrolysis rates under thermalized conditions. Based on the experimental results it is inferred that the hydrolysis rates relate to the intrinsic stability of the M(IV) oxidation states, which correlate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 53 publications
(49 reference statements)
5
57
1
Order By: Relevance
“…This is consistent with fragmentation studies of Pu(IV)(NO 3 ) 5 -reported by Maurice et al [48] which indicate the loss of two NO 2 or N 2 O 4 groups. Fragmentation studies on other metals (Cr, Mn, Fe, Co, Ni, Cu, Zn) in the presence of nitrate have also reported the loss of NO 3 -, NO 2 , or NO molecules and oxidation of the metal [33,64]. Thus, it can be concluded that when nitrate is present in the inner coordination sphere of the metal, CID can lead to oxidation of the metal.…”
Section: Link Between Solution Phase and Gas Phasementioning
confidence: 91%
See 2 more Smart Citations
“…This is consistent with fragmentation studies of Pu(IV)(NO 3 ) 5 -reported by Maurice et al [48] which indicate the loss of two NO 2 or N 2 O 4 groups. Fragmentation studies on other metals (Cr, Mn, Fe, Co, Ni, Cu, Zn) in the presence of nitrate have also reported the loss of NO 3 -, NO 2 , or NO molecules and oxidation of the metal [33,64]. Thus, it can be concluded that when nitrate is present in the inner coordination sphere of the metal, CID can lead to oxidation of the metal.…”
Section: Link Between Solution Phase and Gas Phasementioning
confidence: 91%
“…gas phase behavior [45,47,52,53], Pu(III) gas phase behavior [32,33,44], and Pu(IV) tetrapositive gas phase behavior [48,54]. Rios et al reported in 2011 the gas phase reduction of PuO 2 2? to Pu(V) and Pu(IV), followed by ESI-MS [47], demonstrating parallel rich redox chemistry for Pu in the gas phase and solution phase.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This technique is known to be used in combination with traditional solution chemistry techniques to investigate metal-ligand interactions 45,46 . Actinide species have been studied by ESI-MS since the early 1990's where the use of electrospray mass spectrometry was utilized for the analysis of various elements including U(VI) 47,48 , Th(IV) 49,50,51,52,53,54,55,56,57 , Am(III) 34,58,59,60,61,62,63 , Np and Pu in different oxidation states 64,65,66,67,68,69,70 . The publications range from species identification to specific interest in the chemistry of the f-elements 59,50,71 through the investigation of competitive interactions 54 .…”
Section: To Complement the Characterization An Esi-ms Investigation mentioning
confidence: 99%
“…Additionally, a number of studies have included the use of ESI-MS to investigate the gas phase behavior of UO 2 + , UO 2 2+ , PuO 2 + and PuO 2 2+ 55,72, 65,66,67,73,74,75,76,77 Pu(III) 61,59,60 , Pu(IV) gas phase behavior 59,78 and Rios et al reported the gas phase reduction of PuO 2 2+ to Pu(V) and Pu(IV) followed by ESI-MS 67 . The ESI-MS spectra in positive ionisation mode of 1 after dissolution of some crystals in THF and 1/1000 th dilution in CH 3 CN are reported in the SI (Figure S4 and S5) .…”
Section: To Complement the Characterization An Esi-ms Investigation mentioning
confidence: 99%